PERSONAL RESPONSIBILITY OF THE BOARD OF DIRECTORS TOWARDS COMPANY LOSS USING THE DOCTRINE PIERCING THE CORPORATE VEIL - Guntara, Deny; Gary Gagarin Akbar, Muhammad; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
Management of limited liability companies is carried out daily by the directors. directors have the right and authority to act on behalf of and in the interests of the company within the limits permitted by applicable laws and regulations and their articles of association. However, in practice there are many directors who commit acts against the law to the detriment of others. The problem discussed in this study is how the directors' personal responsibility for company losses using the doctrine of piercing the corporate veil. This research uses the normative juridical method. The conclusion of this study is that directors must carry out their duties and authority in good faith in accordance with the articles of association and legislation. In the company law there is a concept of separation of the company's assets, but this can be set aside by using the doctrine of piercing the corporate veil. if the director makes a mistake or negligence, the board of directors can be sued up to his personal property. This doctrine has been accommodated in Law Number 40 of 2007 concerning Limited Liability Companies so that it has legal certainty for the community.